O krok do Nobla i krok po nim – recepcja twórczości Olgi Tokarczuk na Ukrainie - Nachlik, Olesia (Postscriptum Polonistyczne, 2020)
The paper distinguishes and analyses the interpretative dominants in the Ukrainian reception of Olga Tokarczuk’s work over the last twenty years or so. This reception comprises numerous interviews, public conversations, translations and their presentations, literary criticism and literary studies dissertations, revealing the specificity of the point of view Poland’s neighbouring culture has on works which are now part of the world literature canon.